Bauran Pemasaran, Manajemen Hubungan Pelanggan dalam Menciptakan Loyalitas Konsumen - Tauriana, Dian; Andhika, Andhika (Journal the Winners: Economics, Business, Management, and Information System Journal, 2010)
The more advanced development of the business world led to the emergence of an increasingly tight competition, which challenge must be faced by PT Serafim Tours and Travel by conducting strategic steps. Maintaining the viability of the company can be achieved by gaining consumer loyalty. To achieve such loyalty is to utilize existing marketing concepts, namely the marketing mix and Customer Relationship Management (CRM). It is important to understand consumers' needs very well (fast and accurate). Through the concept of marketing mix, to think about how your product or service is packaged, giving a brand, having characteristics, level of prices offered, level of discount given, how the products or services are distributed and the latter, through what media service the product will be known. The presence of the CRM will be able to cope with consumer demand since the aim of CRM is to get the core concept of customer that is not obvious and put it in terms of company applications framework. This paper reviews the theory and implementation of marketing mix and CRM and its influence on customer loyalty by using path analysis.